Radix isatidis Polysaccharides Inhibit Influenza a Virus and Influenza A Virus-Induced Inflammation via Suppression of Host TLR3 Signaling In Vitro - Li, Zhengtu (Molecules, 2017)
Influenza remains one of the major epidemic diseases worldwide, and rapid virus replication and collateral lung tissue damage caused by excessive pro-inflammatory host immune cell responses lead to high mortality rates. Thus, novel therapeutic agents that control influenza A virus (IAV) propagation and attenuate excessive pro-inflammatory responses are needed. Polysaccharide extract from Radix isatidis, a traditional Chinese herbal medicine, exerted potent anti-IAV activity against human seasonal influenza viruses (H1N1 and H3N2) and avian influenza viruses (H6N2 and H9N2) in vitro. The polysaccharides also significantly reduced the expression of pro-inflammatory cytokines (IL-6) and chemokines (IP-10, MIG, and CCL-5) stimulated by A/PR/8/34 (H1N1) at a range of doses (7.5 mg/mL, 15 mg/mL, and 30 mg/mL); however, they were only effective against progeny virus at a high dose. Similar activity was detected against inflammation induced by avian influenza virus H9N2. The polysaccharides strongly inhibited the protein expression of TLR-3 induced by PR8, suggesting that they impair the upregulation of pro-inflammatory factors induced by IAV by inhibiting activation of the TLR-3 signaling pathway. The polysaccharide extract from Radix isatidis root therefore has the potential to be used as an adjunct to antiviral therapy for the treatment of IAV infection.